PENGARUH MODEL PEMBELAJARAN INKUIRY TERBIMBING TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS V SD INPRES MALENGKERI BERTINGKAT 1 - Umul Khaira Aulia; Nurlina Nurlina; Amri Amal (Universitas 45 Surabaya, 2023)
This study aims: To determine whether there is an effect of the guided inquiry learning model on the heat material science process skills of the fifth grade students of SD Inpres Malengkeri Rank 1, Tamalate District. To find out there is an influence of the guided inquiry learning model on science learning outcomes on heat transfer material for fifth grade students of SD Inpres Malengkeri Rank 1, Tamalate District. Based on the results of the research above, it can be concluded that the guided inquiry model has an influence on science learning outcomes in fifth grade students of SD Inpres Malengkeri Stratified. This study used a quantitative approach with a quasi-experimental method involving 60 samples based on the sample population of class V at SD Inpres Malengkeri Rank 1. Which was divided into two classes, namely the experimental class and the control class, then pre-test and post-test were carried out in the two classes. the. The results of this study indicate that the application of the guided inquiry learning model descriptively can be argued that the science process skills average score of the experimental class is 96.00 while that of the control class is 77.83. Whereas in the learning outcomes the average value of the experimental class was 85.40, while the control class was 75.60. Based on the results of the analysis of the Multivariate Tests, it shows that in the generative row, the significance value for both Pillai Trace, Wilks' Lambda, Hotteling's Trace and Roy's Lergest Root is 0.000 <0.05 or smaller than the r-table. So thus Ho is rejected and Ha is accepted, so the effect of the guided inquiry learning model on science process skills and science learning outcomes on heat transfer material for class V SD Inpres Malengkeri Level 1, Tamalate District.